The Spartan King Leonidas I: History and modern times - E.A. Tchiglintsev; N.A. Shadrina (Ученые записки Казанского университета: Серия Гуманитарные науки, 2017)
The image of the King Leonidas I was formed based on the evidence documented by Herodotus. The evidence includes all the variations of the Spartan king's image that have been reflected in the cultures of the consequent periods, especially the symbolic meaning of his image for the Greeks. Herodotus's image of Leonidas I was criticized by Plutarch (in his On the Malice of Herodotus) and admired by Pausanias. The appeal to the image of the King Leonidas I in the European culture of the consequent centuries is determined by the social and cultural conditions in which the need for recourse to the events of the 5th century BC appeared. Anti-tyrannical ideas and the cult of freedom as opposed to slavery inspired the artists of the 17th – 18th centuries (Henry Purcell, Richard Glover) to create their poems celebrating the heroic ideal of Leonidas I. The European Romantic poets of the first half of the 19th century were inspired by the image of Leonidas I because of their sympathy to the struggle for freedom of the Greeks (Michel Pichat, Lord Byron, and Alexander Pushkin in Russia). Victor Hugo raises the conflict of the Greeks and the Persians to the mythological level describing it as a civilizations confrontation. The image of the King Leonidas I in the European culture at the end of the 19th and the first half of the 20th centuries was revived due to world wars. In the second half of the 20th century and in the first decade of the 21st century, the image of the King Leonidas I in art to greater extend turns to the purposes of entertainment (Valerio Manfredi's novel, Rudolph Mate's movie, and especially the graphic novel by Frank Miller and the cinematographic movie by Zack Snyder titled “300” adapted from it). While the novelists describe Leonidas I as a tragic personality, the authors of the comics only invest him with functions attributable to the stereotypic visions of a hero.